t-PA, but not desmoteplase, induces plasmin-dependent opening of a blood-brain barrier model under normoxic and ischaemic conditions - Freeman, Roxann; Niego, Be׳eri; R. Croucher, David; Pedersen, Lars O.; Medcalf, Robert L. (Brain research, 2014)
Tissue-type plasminogen activator (t-PA) is the only thrombolytic treatment available for patients with acute ischaemic stroke. However, t-PA can increase permeability of the blood-brain barrier (BBB). Desmoteplase is a plasminogen activator derived from the common vampire bat, currently under clinical development for ischaemic stroke. We compared how t-PA and desmoteplase influenced BBB permeability using a human in vitro model where primary brain endothelial cells (BEC) and astrocytes are co-cultured on the opposite sides of a porous membrane. Permeability changes were evaluated 6 or 24h post-stimulation by passage of fluorescent albumin across the membrane. Under normoxic conditions, t-PA, but not desmoteplase, increased BBB permeability. Surprisingly, the ability of t-PA to affect the barrier was lost under conditions of oxygen-glucose deprivation (OGD). Addition of plasminogen re-sensitised the BBB to the action of t-PA under both normoxia and OGD, but did not affect the inert behaviour of desmoteplase, even when digested fibrinogen was added to ensure optimal plasmin generation. These observations coincided with plasmin-dependent changes in astrocyte and BEC morphology and disruption of tight junction proteins in BECs, specifically initiated by t-PA but not by desmoteplase. Finally, inhibition of plasmin post-stimulation with t-PA and plasminogen, especially within 2h, protected the BBB against t-PA-mediated barrier opening. Hence t-PA, but not desmoteplase, increases BBB permeability under both normoxic and OGD conditions in a reversible, plasmin-dependent process. The inability of desmoteplase to increase permeability despite its capacity to generate plasmin provides further support for its use as thrombolytic in patients with ischaemic stroke. •t-PA but not desmoteplase increases blood-brain barrier (BBB) permeability in vitro.•Ischaemic conditions attenuate the action of t-PA on BBB permeability.•The increase in BBB permeability by t-PA is reversible only within 2h of onset.•t-PA and desmoteplase bind to LRP-1 with similar affinity.•Desmoteplase does not antagonise the ability of t-PA to increase permeability.